What is Actually Influencing the Purchasing Decisions of Customers? - Ilham Qodri Romadhon; Masruri; Bella Suci Novitri (Journal of Islamic Enterpreneurship and Management, 2025)
ShopeeFood, as one of the major players, faces challenges related to an inefficient brand image, product quality complaints from customers, and suboptimal marketing strategies that could potentially influence consumer purchasing decisions. This study aims to analyze and test the influence of brand image, product quality, and marketing strategies on purchasing decisions among ShopeeFood users in Pasar Kemis Subdistrict, Tangerang Regency, both partially and simultaneously. The sampling technique used is non-probability sampling with the Lemeshow formula, resulting in 97 respondents selected based on specific criteria. The results of the study indicate that, partially, the brand image variable has a positive and significant influence on purchasing decisions with a t-value greater than the t-table value 2.230>1.6614 at a significance level of 0.0291.6614 and a statistical significance of 0.096>0.05, The marketing strategy variable does not have a significant effect on purchasing decisions, with a calculated t-value of 0.1960.05. The simultaneous results show that brand image, product quality, and marketing strategy collectively have a positive and significant effect on purchasing decisions. This is evidenced by the F-test results, with the calculated F-value greater than the table F-value 45.129>2.70 and a significance level of 0.000<0.05.